2014
DOI: 10.1186/1471-2393-14-267
|View full text |Cite
|
Sign up to set email alerts
|

Thermal care for newborn babies in rural southern Tanzania: a mixed-method study of barriers, facilitators and potential for behaviour change

Abstract: BackgroundHypothermia contributes to neonatal morbidity and mortality in low-income countries, yet little is known about thermal care practices in rural African settings. We assessed adoption and community acceptability of recommended thermal care practices in rural Tanzania.MethodsA multi-method qualitative study, enhanced with survey data. For the qualitative component we triangulated birth narrative interviews with focus group discussions with mothers and traditional birth attendants. Results were then cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 33 publications
7
63
0
1
Order By: Relevance
“…In the study area, the practice of wrapping the baby immediately after birth in the same cloth used for drying is a practice likely to increase the risk of hypothermia and infection in newborns. Barriers and facilitators to appropriate care in this area are similar to those found in other settings [16,29,30]. …”
Section: Discussionsupporting
confidence: 72%
“…In the study area, the practice of wrapping the baby immediately after birth in the same cloth used for drying is a practice likely to increase the risk of hypothermia and infection in newborns. Barriers and facilitators to appropriate care in this area are similar to those found in other settings [16,29,30]. …”
Section: Discussionsupporting
confidence: 72%
“…Previously, Mangwi et al and Byaruhanga et al have reported sub optimal thermal care among women of the general reproductive age [27,34]. Among adolescent mothers and some health workers, poor knowledge and poor acceptance of simple methods to maintain a warm chain from birth till the end of the neonatal period have been documented as risk factors for poor neonatal thermal care [25,27,31,34,35]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have established poor SSC practices by mothers in various rural African settings [47,48]. [49]. According to the WHO, SSC is a highimpact intervention that supports the establishment of exclusive breastfeeding, assists with appropriate thermal care and promotes bonding between mother and newborn [50].…”
Section: Plos Onementioning
confidence: 99%